Virulence Associated Genes-Deleted Salmonella Montevideo Is Attenuated, Highly Immunogenic and Confers Protection against Virulent Challenge in Chickens - Lalsiamthara, Jonathan; Lee, John H. (Frontiers in Microbiology, 2016)
To construct a novel live vaccine against Salmonella enterica serovar Montevideo (SM) infection in chickens, two important bacterial regulatory genes, lon and cpxR, which are associated with invasion and virulence, were deleted from the wild type SM genome. Attenuated and highly immunogenic strains, JOL1625 (∆lon), JOL1597 (∆cpxR), and JOL1599 (∆lon∆cpxR) were thereby generated. Observations with scanning electron microscopy suggested that JOL1625 and JOL1599 cells showed increased ruffled surface which may be related to abundant extracellular polysaccharide (EPS) production. JOL1597 depicted milder ruffled surface but showed increased surface corrugation. ConA affinity-based fluorometric quantification and fluorescence microscopy revealed significant increases in extracellular polysaccharide (EPS) production in JOL1625 and JOL1599. Four weeks old chickens were used for safety and immunological studies. The mutants were not observed in faeces beyond day 3 nor in spleen and cecum beyond day 7, whereas wild type SM was detected for at least 2 weeks in spleen and cecum. JOL1599 was further evaluated as a vaccine candidate. Chickens immunized with JOL1599 showed strong humoral responses, as indicated by systemic IgG and secretory IgA levels, as well as strong cell-mediated immune response, as indicated by increased lymphocyte proliferation. JOL1599-immunized groups also showed significant degree of protection against wild type challenge. Our results indicate that ∆lon- and/or ∆cpxR-deleted SM exhibited EPS-enhanced immunogenicity and attenuation via reduced bacterial cell intracellular replication, conferred increased protection, and possess safety qualities favorable for effective vaccine development against virulent SM infections.